Integration of Financial Markets During Covid-19: A Dynamic Correlation Analysis on Euronext - Espinosa-Mendez, C (Routledge, 2023)
This article investigates the reaction of integrated financial markets to the COVID-19 pandemic. Using a dynamic conditional correlation model on Euronext Stock Exchange, I find that the integration of financial markets can act as a buffer against negative shocks such as COVID-19. However, this benefit begins to fade as the number of deaths from COVID-19 increases. In this case, a negative relationship with the dynamic correlation is found in some pairs of member countries. © 2021 Informa UK Limited, trading as Taylor & Francis Group.